Kaedah Tafsir Abdur Rahman Al-Sa'di Dalam Kitab Al-Qawaid Al-Hisan Li Al-Tafsir Al-Qur'an - Nofmiyati Nofmiyati; Miftahuddin Miftahuddin (Madania: Jurnal Ilmu-Ilmu Keislaman, 2020)
There were those who thought  the interpretation rules compiled by the scholars were binding and might be followed by other commentators, there were also those who Saw them were not binding as they were only as a work procedure for a commentator. Nevertheless the rules of interpretation compiled by the scholars remained important.